Wakamono Kotoba dalam Anime "Gekkan Shoujo Nozaki-Kun" (Yamazakie, 2014) - Wartini, Hani Santika; Martawijaya, Asteria Permata; Putri, Intan Dwi Dahidi (Jurnal SORA - Pernik Studi Bahasa Asing, 2024)
This study examines wakamono kotoba contained in the anime "Gekkan Shoujo Nozaki-kun". The purpose of this study is to describe the types and processes of formation of wakamono kotoba contained in the anime "Gekkan Shoujo Nozaki-kun". The method used in this study is a qualitative descriptive using the technique of listening to and recording in data collection. After the data is collected, the data is analyzed with qualitative analysis techniques. The results showed that there are 261 wakamono kotoba data in the anime "Gekkan Shoujo Nozaki-kun" divided into 6 types, namely shouryakugo (49 data), kyouchougo (5 data), giongo-gitaigo (3 data), kogo (2 data), hougen (3 data), and gairaigo (159 data). Through the theory of Japanese word formation (gokeisei), it was found that the wakamono kotoba contained in the anime "Gekkan Shoujo Nozaki-kun" was formed through haseigo (3 data), karikomi/shouryaku (49 data), fukugougo/giseigo (1 data), and toujigo (2 data). Based on the large amount of data, it can be understood that most wakamono kotoba comes from the absorptive language (gairaigo), and is formed through abbreviation (shouryaku).